Does intellectual property protection stimulate digital economy development? - Wen Chen; Ying Wu (Journal of Applied Economics, 2022)
The digital economy plays an important role in society and the economy. However, we know little about what factors affect the development of the digital economy. Using a self-developed index for measuring Chinese provincial-level digital economy development, this paper examines the impact of intellectual property protection on the digital economy. We find that there is a U-shaped relationship between intellectual property protection and digital economy. Our findings remain valid after a battery of robustness tests. Our findings support the importance of intellectual property protection in developing the digital economy.
Keywords: 330; Digital economy; intellectual property protection; U-shaped relationship